The psychosocial impact of climate change among smallholder farmers: a potential threat to sustainable development - Shoko Kori, Dumisani (Frontiers in Psychology, 2023)
Psychosocial impacts of climate change and implications on sustainable development remain unclear. This problem was addressed focusing on smallholder farmers in resettlement areas of Chirumanzu District, Zimbabwe. An Exploratory Descriptive Qualitative research design was adopted. Purposive sampling techniques were used to select fifty-four farmers who served as main respondents from four representative wards. Data were collected through semi-structured interviews and analyzed using thematic content analysis. Code groups and codes were established through inductive approaches considering narratives of farmers. Forty psychosocial impacts were established. They were qualitative, intangible, indirect and difficult to measure quantitatively. Farmers agonized over the threat of climate change on farming operations, felt humiliated and embarrassed over detestable practices they resorted to due to climate change. Some farmers experienced heightened negative feelings, thoughts and emotions. It was established that psychosocial impacts of climate change have a strong bearing on sustainable development of emerging rural communities.